Antibacterial activity of essential oils from some Artemisia and Thymus species against methicillin-resistant Staphylococcus aureus (Experimental biology, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) is the causative agent of many diseases, firstly, of skin and soft tissues infections. The emergence of antibiotic-resistant strains, such as MRSA requires the search for new agents to withstand this pathogen, in particular among natural compounds. Essential oils are natural organic compounds that have a wide spectrum of biological activity: antimicrobial, antiviral, antioxidant, anti-inflammatory and immunomodulattory. The present work for the first time has determined an antibacterial activity of essential oils isolated from 5 plants of Kazakhstan: Artemisia kotuchovii Kupr., Artemisia scoparia Waldst. et Kit., Thymus crebrifolius (Klokov), Thymus marschallianus Willd. and Thymus rasitatus (Klokov) in regard to MRSA USA300. Antibacterial activity of essential oils was defined by measuring the light absorption kinetics of bacterial suspension using calculation of the inhibitory concentration (IC25) at which the growth of microorganisms was inhibited to 25%. A. scoparia, T. marschallianus and Т. rasitatus essential oils (IС25 = 24.5; 30.9 and 32.7 μg/ml, respectively) possess the high inhibitory effect on increase of MRSA; T. crebrifolius essential oil showed low activity (IС25 = 73.0 μg/ml). A. kotuchovii essential oil did not show activity even at the highest tested concentration of 100 μg/ml.
Keywords: essential oils, antibacterial activity, methicillin-resistant Staphylococcus aureus (MRSA).